Indistinguishable MHz-narrow heralded photon pairs from a whispering gallery resonator - Sheng-Hsuan Huang; Thomas Dirmeier; Golnoush Shafiee; Kaisa Laiho; Dmitry V. Strekalov; Andrea Aiello; Gerd Leuchs; Christoph Marquardt (APL Photonics)
The Hong–Ou–Mandel interference plays a vital role in many quantum optical applications where indistinguishability of two photons is important. Such photon pairs are commonly generated as the signal and idler in the polarization-degenerate spontaneous parametric downconversion (SPDC). To scale this approach to a larger number of photons, we demonstrate how two independent signal photons radiated into different spatial modes can be rendered conditionally indistinguishable by a heralding measurement performed on their respective idlers. We use the SPDC in a whispering gallery resonator, which is already proven to be versatile sources of quantum states. Its extreme conversion efficiency allowed us to perform our measurements with only 50 nW of in-coupled pump power in each propagation direction. The Hong–Ou–Mandel interference of two counterpropagating signal photons manifested itself in the fourfold coincidence rate, where the detection of two idler photons heralds a pair of signal photons with a desired temporal overlap. We achieved the Hong–Ou–Mandel dip contrast of 74% ± 5%. Importantly, the optical bandwidth of all involved photons is of the order of a MHz and is continuously tunable. This, on the one hand, makes it possible to achieve the necessary temporal measurement resolution with standard electronics and, on the other hand, creates a quantum state source compatible with other candidates for qubit implementation, such as optical transitions in solid-state or vaporous systems. We also discuss the possibility of generating photon pairs with similar temporal modes from two different whispering gallery resonators.